Awareness and Knowledge of Medical, Nursing and Midwifery Students About Human Papillomavirus Infection and its Vaccine in Ahvaz Jundishapur University of Medical Sciences in 2020 - Abdolhussein Shakurnia; Ata Ghadiri; Niloofar Jelodar; Maedeh Hamidi (Zanjan University of Medical Sciences and Health Services, 2022)
Background: Human papillomavirus (HPV) infection is the most common sexually transmissible infection, which has a key role in the development of cervical cancer. Objectives: This study aimed to assess the level of awareness/knowledge among medical, nursing and midwifery students about HPV infection and its vaccine in Ahvaz Jundishapur University of Medical Sciences (AJUMS) in 2020. Methods: This cross-sectional study was conducted on 181 medical, nursing and midwifery students who were selected based on convenience sampling. Students' awareness/knowledge were assessed through a validated questionnaire consisted of 15 correct and incorrect questions with a score range of 0-15. Data were analyzed using Chi-square test and logistic regression by SPSS-18. Results: The mean (SD) of age of the participants was 25.4 (1.84) years, and the majority of them were female (60.2%) and single (79.6%). Overall, the students' awareness/knowledge score about HPV was 66.92 (22.8) (out of 100). The mean (SD) of awareness/knowledge of female students was higher than male students 68.8 (18.5) vs 64.1 (28.1), but there was no statistically significant (p=0.210). The awareness/knowledge among the medical students was significantly higher than that of the nursing and midwifery students (t179=7.17, p˂0.001). Significant odds ratio (OR) for predictors to good awareness/knowledge were higher age (OR=0.76, p = 0.023), higher grade point average (OR=1.49, p=0.030), and medical students' group (OR=17.31, p˂0.001). Conclusion: Although the awareness/knowledge of students in this study was above average, which highlights the need for education measures to improve awareness/knowledge of students regarding HPV, since they will be future health care providers in society.